2020
DOI: 10.1177/2150132720965077
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Experienced by Physicians

Abstract: Purpose: World Health Organization (WHO) defines intimate partner violence (IPV) as physical, sexual or psychological harm caused by an intimate partner or ex-partner. There are few studies describing interpersonal violence (IPV) among physicians. Our study describes IPV experienced by U.S. physicians. Methods: This was a multicenter survey administered to 4 physician groups in 2015 to 2016. In total 400 respondents returned survey results. Measures included current IPV, childhood abuse, mental health, profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
2
5
0
1
Order By: Relevance
“…Online Supplemental Appendix D (Table) contains details (including statistics as reported in studies) on risk markers. As well as being female, a nurse or from a LMIC, the following risk markers were associated with experiences of DVA: ethnicity (though no clear pattern emerged about the ethnic groups most at risk) ( Bracken et al, 2010 ; Doyle et al, 1999 ; Reibling et al, 2020 ); increasing number of, or having no, children ( Aguocha et al, 2017 ; Shokre & Ahmed, 2017 ) (although Çakmak Pekşen and Şahin (2019) found number of children was not related) and financial factors. Specifically, women who were dependent solely on their own salary, women whose husbands were unemployed and women who contributed a greater share to household expenses were more likely to experience DVA ( Carmona-Torres et al, 2018 ; Sharma & Vatsa, 2011 ; Shokre & Ahmed, 2017 ) – although Bracken et al (2010) found no association with income itself.…”
Section: Resultsmentioning
confidence: 99%
“…Online Supplemental Appendix D (Table) contains details (including statistics as reported in studies) on risk markers. As well as being female, a nurse or from a LMIC, the following risk markers were associated with experiences of DVA: ethnicity (though no clear pattern emerged about the ethnic groups most at risk) ( Bracken et al, 2010 ; Doyle et al, 1999 ; Reibling et al, 2020 ); increasing number of, or having no, children ( Aguocha et al, 2017 ; Shokre & Ahmed, 2017 ) (although Çakmak Pekşen and Şahin (2019) found number of children was not related) and financial factors. Specifically, women who were dependent solely on their own salary, women whose husbands were unemployed and women who contributed a greater share to household expenses were more likely to experience DVA ( Carmona-Torres et al, 2018 ; Sharma & Vatsa, 2011 ; Shokre & Ahmed, 2017 ) – although Bracken et al (2010) found no association with income itself.…”
Section: Resultsmentioning
confidence: 99%
“…Discuss this article at www.facebook.com/ MDedgePsychiatry recent stalking by a current or former intimate partner. 9 When a person who is a victim of intimate partner violence is also stalked as part of the abuse, homicide risk increases. 10 Workplace homicides of health care professionals are most likely to be committed by a current or former partner or other personal acquaintance, not by a patient.…”
Section: Clinical Pointmentioning
confidence: 99%
“…[ 9 ] Physicians should be taught objective assessment models and the implications of using those models in practice; however, the first step is to appreciate what it’s like to be submissive in an abusive household. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%